Domestic Component Level in Road Construction Projects Regarding the Regulation of Regulation of the Minister of Industry and Decree of the Minister of Public Works and Public Housing - Berman, Berman; Kurniyaningrum, Endah; Yuwono, Bambang Endro; Pontan, Darmawan (Newinera Publisher, 2024)
Indonesia's economic growth occurs in all business fields, one of which is the construction sector, this shows that, the construction sector contributes significantly to the country's economic growth. . The purpose of this study will analyze the application of DCL to government regulatory policies, this research method takes case studies on 3 (three) infrastructure projects with vendor selection using 2 (two) alternatives. Alternative 1 uses the selected vendor with the highest DCL value and alternative 2 uses the selected vendor based on the highest rating from the Final Evaluation Results (FER). From the results of the analysis, it was obtained that the implementation of DCL based on the regulation of the Minister of Industry No. 16 of 2011 still met the minimum of 40%, while the amount of DCL based on the regulation of the Ministry of PUPR No. 602/KPTS/M/2023 did not meet the minimum value of 70%. Meanwhile, from the analysis, it was also found that, by maximizing the DCL value, it will have an impact on high price bids, so that the price submitted during tendering will be less competitive and tend to experience price defeat during tendering.